Commentary: The power of print remains undiminished - Tim Pankhurst (Asia Pacific Network, 2008)
The Dominion Post editor Tim Pankhurst, whose newspaper celebrated its centenary in 2007, outlines the innovations undertaken by his newspaper in meeting the technological challenges of the mainstream media.